Tppp3 is a novel molecule for retinal ganglion cell identification and optic nerve regeneration - Mishal Rao; Ziming Luo; Chia-Chun Liu; Chi-Yu Chen; Shining Wang; Michael Nahmou; Bogdan Tanasa; Aman Virmani; Leah Byrne; Jeffrey L. Goldberg; José-Alain Sahel; Kun-Che Chang (Acta Neuropathologica Communications)
Abstract Mammalian central nervous system (CNS) axons cannot spontaneously regenerate after injury, creating an unmet need to identify molecular regulators to promote axon regeneration and reduce the lasting impact of CNS injuries. While tubulin polymerization promoting protein family member 3 (Tppp3) is known to promote axon outgrowth in amphibians, its role in mammalian axon regeneration remains unknown. Here we investigated Tppp3 in retinal ganglion cells (RGCs) neuroprotection and axonal regeneration using an optic nerve crush (ONC) model in the rodent. Single-cell RNA sequencing identified the expression of Tppp3 in RGCs of mice, macaques, and humans. Tppp3 overexpression enhanced neurite outgrowth in mouse primary RGCs in vitro, promoted axon regeneration, and improved RGC survival after ONC. Bulk RNA sequencing indicated that Tppp3 overexpression upregulates axon regeneration genes such as Bmp4 and neuroinflammatory pathways. Our findings advance regenerative medicine by developing a new therapeutic strategy for RGC neuroprotection and axon regeneration.